Automated System for Multiversion Setting and Solving of Design Problems in the Initial Stages of Remote Sensing Satellites Conceptual Designing Process. (2015) - Kirilin, Alexander; Akhmetov, Ravil'; Kurenkov, Vladimir; Stratilatov, Nikolay; Abrashkin, Valeriy; Kucherov, Alexander; Safronov, Sergey; Yakishchik, Artyom
Abstract: Methodology and software for multiversion setting and solution of high dimension design problems was developed. With simple examples, possibility of development of advanced bundled software, which allows updating the spacecraft design in real-time mode, is demonstrated. Mathematical models being in use in aerospace industry were applied.